"Housing Is Health Care": Treating Homelessness in Safety‐net Hospitals. (11th November 2021) - Hanssmann, Christoph; Shim, Janet K.; Yen, Irene H.; Fleming, Mark D.; Van Natta, Meredith; Thompson‐Lastad, Ariana; Rasidjan, Maryani Palupy; Burke, Nancy J.
Abstract: As medicine integrates social and structural determinants into health care, some health workers redefine housing as medical treatment. This article discusses how health workers in two U.S. urban safety‐net hospitals worked with patients without stable housing. We observed ethnographically how health workers helped patients seek housing in a sharply stratified housing economy. Analyzing in‐depth interviews and observations, we show how health workers: (1) understood housing as health care and navigated limits of individual care in a structurally produced housing crisis; and (2) developed and enacted practices of biomedical and sociopolitical stabilization, including eligibilizing and data‐tracking work. We discuss how health workers bridged individually focused techniques of clinical care with structural critiques of stratified housing economies despite contradictions in this approach. Finally, we analyze the implications of providers' extension of medical stabilization into social, economic, and political realms, even as they remained caught in the structural dynamics they sought to address.